1983
DOI: 10.1021/ja00348a007
|View full text |Cite
|
Sign up to set email alerts
|

Steric forces in substituted aromatics: conformation of the hexahalobenzenes as determined by ab initio calculations

Abstract: The fully halogenated benzenes C6F6, C6C16, C6Br6, and C6I6 have been studied in a series of all-electron ab initio Hartree-Fock calculations using basis sets of double-¿"quality or better. Geometry optimizations have been performed with the aim of resolving controversies among experimental results with regard to the planarity of the heavier molecules in the series. The compounds are all found to be planar, and the present results therefore reject the notion of geometrical distortions due to steric overcrowdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The tilting of the iodine atoms away from the benzene plane is very small and almost within the standard deviations of the experiments. There has been agreement of the results regarding these structural characteristics in all studies based on single crystal X-ray diffraction [9], gas phase electron diffraction (except for C 6 I 6 ) [10], vibrational [11] and photoelectron spectroscopy [12], and quantum chemical calculations [13].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The tilting of the iodine atoms away from the benzene plane is very small and almost within the standard deviations of the experiments. There has been agreement of the results regarding these structural characteristics in all studies based on single crystal X-ray diffraction [9], gas phase electron diffraction (except for C 6 I 6 ) [10], vibrational [11] and photoelectron spectroscopy [12], and quantum chemical calculations [13].…”
Section: Introductionmentioning
confidence: 60%
“…Surprisingly, however, the idea that the phenomenon could also be strongly influenced by attractive instead of repulsive forces was rarely considered [13].…”
Section: Introductionmentioning
confidence: 99%
“…10 This discrepancy has been previously noted. 11 This pattern of large discrepancies between theory and experiment for modes that are forbidden in optical spectroscopies suggested that an inelastic neutron scattering (INS) study would be in order. This method of vibrational spectroscopy is not restricted by selection rules.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred conformations of a number of polychlorinated biphenyls (PCBs) has been determined by STO-3G calculations (56) and a consequent binding model proposed to explain PCB and dioxin cytosol binding (57). The hexahalobenzenes (C,F(,, CXCl6, C6Br6, and C6I6) have been shown (58) to be planar in a double-zeta quality calculation (444 basis functions for C616().…”
Section: Calculations: Complete Optimizationmentioning
confidence: 99%